On-Road Car Breakdown Assistant Finder - Aman, Hannani; Zainodin, Mohamad Akmal (Applied Information Technology And Computer Science, 2020)
A car breakdown on the road can be dangerous to the car or the driver itself. Car trouble can happen anytime, anywhere, and anyone. In this paper, an on-road car breakdown assistant finder is designed to manage the on-road car Breakdown sys-tematically near Parit Raja. Where the mechanic offers a workshop repairing vehicles, selling replacement parts and towing services. This new computerized system is created to be used by them so that it will lighten their burden. This propose project system is a customized web application where a mechanic can be alerted when the customer has urgent requests for car problems. The system allows the customer to send their location and select the services needed. Admin handles and can access the user details as well as the mechanic details. The admin has access to allow/block and view the mechanics. This online mechanic locator reduces customer work and can easily find the mechanics from the area, thus minimizes the customer time and cost. The language that is going to be use is a PHP, XAMPP and MySQL database to develop the system. As for analysis and design phase, a flowchart, Entity Relationship Diagram(ERD), both level 0 and 1 Data Flow Diagram(DFD) and interface design. By developing this system in mission to help a stranded driver in Parit Raja in finding nearest mechanic in the area. This system able the driver to find the nearest mechanic in the area base on their location by using global positioning system.